The Influence of MAC Protocol on a Non-Synchronous Localization Scheme in Large-Scale UWSNs - Keyu Chen (IEEE Access, 2018)
Localization plays a more and more important role in underwater wireless sensor networks (UWSNs). But in the large-scale UWSNs, the localization algorithm can’t be realized for the continuous packet collision. Therefore, we need to consider the impact of MAC protocol on the positioning algorithm. First, this paper proposes a multi-layer positioning model based on the underwater network architecture. Then according to the non-synchronous localization scheme, we analyze the reason of packet collisions and propose the variable interval ALOHA (VI-ALOHA) protocol based on the Poisson distribution. The VI-ALOHA protocol reduces the collision by adding random space–time. Through the comparison of localization coverage, packet loss, and localization time, this paper evaluates the impact on the localization result in equal interval ALOHA (EI-ALOHA) and VI-ALOHA. Our simulation results show that the MAC protocol has a significant influence on localization; besides, the localization coverage and the packet loss of VI-ALOHA protocol are above 20% better than the EI-ALOHA.